2017
DOI: 10.1200/jco.2017.35.15_suppl.e21570
|View full text |Cite
|
Sign up to set email alerts
|

Neo-adjuvant chemotherapy and distress in breast cancer patients: The moderating role of generalized self-efficacy.

Abstract: e21570 Background: Neo-Adjuvant Chemotherapy (NAC) is commonly recommended as a preoperative treatment for patients with locally advanced breast cancers (BC). However, several studies have shown that NAC can increase patients’ distress. A first aim of this study was to evaluate if BC patients treated with NAC show higher levels of distress as compared to patients undergoing primary surgery (PS). A secondary aim was to evaluate if distress could be significantly correlated with patients’ depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, NAC has been associated with higher levels of psychological distress, which have been linked to anxiety and depression. 32 A study of infertile women demonstrated that patients who screened positive for depression were less likely to initiate fertility treatments, highlighting the complexity of potential factors that enter into the decisional calculus regarding fertility treatment. 33 While the finding that receipt of NAC was associated with less-frequent acceptance of REI referral is novel and significant on its own, it becomes even more important in the context of a recent multicenter study that demonstrated that NAC was an independent negative predictor of completing ovarian stimulation following REI consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NAC has been associated with higher levels of psychological distress, which have been linked to anxiety and depression. 32 A study of infertile women demonstrated that patients who screened positive for depression were less likely to initiate fertility treatments, highlighting the complexity of potential factors that enter into the decisional calculus regarding fertility treatment. 33 While the finding that receipt of NAC was associated with less-frequent acceptance of REI referral is novel and significant on its own, it becomes even more important in the context of a recent multicenter study that demonstrated that NAC was an independent negative predictor of completing ovarian stimulation following REI consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy generates a distress that, over time, can severely affect patient quality of life [ 47 , 48 ]. A recent study showed that post-NAC patients have a significantly higher level of distress compared to patients receiving chemotherapy after surgery [ 49 ]. Understanding the needs of patients undergoing NAC enables us to address the communication process more appropriately, provide psychological support, and build clinical and rehabilitation interventions in a more personalized way [ 47 ].…”
Section: The Neoadjuvant Supportive Care Teammentioning
confidence: 99%